Kekuatan Politik Islam dalam Masyarakat Jejaring: Studi Komparatif Strategi Komunikasi Digital PKS, PKB, dan PPP - Muhamad Febri Ramdani; Alya Putri Mulyani (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to analyze and compare the digital communication strategies of three Islamic-based political parties in Indonesia: the Prosperous Justice Party (PKS), the National Awakening Party (PKB), and the United Development Party (PPP) within the context of corporate communication in the digital era. The study employs a systematic documentary review method by observing digital artifacts on six major platforms, namely Facebook, YouTube, Instagram, X, TikTok, and official websites, during December 2–15, 2025. Data were analyzed using descriptive statistical methods and mapped through a two-dimensional matrix based on content volume and platform diversification thresholds, supported by Manuel Castells’ Network Society theory. The findings reveal differences in digital communication performance despite shared ideological backgrounds. PKS demonstrates the strongest strategy, classified in the high dissemination and high content category with an average of 17 posts per day across five platforms. PKB is categorized as high dissemination and low content with 12 posts per day across four platforms, while PPP shows limited digital activity with one post per day on a single platform. The study concludes that digital political power in the network society is influenced more by organizational capacity and adaptation to digital media dynamics than by ideological orientation alone.